Eye Movements Reveal Delayed Use of Construction-Based Pragmatic Information During Online Sentence Reading: A Case of Chinese Lian…dou Construction - Zang, Chuanli; Zhang, Li; Zhang, Manman; Bai, Xuejun; Yan, Guoli; Jiang, Xiaoming; He, Zhewen; Zhou, Xiaolin (Frontiers in Psychology, 2019)
An ERP study demonstrated that construction-based pragmatic constraints in Chinese (e.g., lian…dou that constrains a low-likelihood event and is similar to even in English) can rapidly influence sentence comprehension and the mismatch of such constraints would lead to increased neural activity on the mismatching word. Here we examine to what extent readers’ eye movements can instantly reveal the difficulties of mismatching constraints when participants read sentences with the structure lian + determiner phrase + object noun + subject noun + dou + verb phrase (VP) + final commenting clause. By embedding high-likelihood or neutral events in the construction, we created incongruent and underspecified sentences and compared such sentences with congruent ones describing events of low expectedness. Relative to congruent sentences, the VP region of incongruent sentences showed no significant differences on first-pass reading time measures, but the total fixation duration was reliably longer. Moreover, readers made more regressions from the VP and the sentence-final region to previous regions in the incongruent than the congruent condition. These findings suggest that the effect of pragmatic constraints is observable during naturalistic sentence reading, reflecting the activation of the construction-based pragmatic information for the late integration of linguistic and extra-linguistic information at sentential level.